MEMBENTUK PEMAIN TIM YANG MEMENUHI PERSYARATAN KOMPETENSI INTERPERSONAL UNTUK BEKERJA TIM: TERAPAN DALAM PRAKTEK MANAJEMEN SUMBERDAYA MANUSIA - Noviaty Kresna Darmasetiawan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2002)
This study of team gives a review of the conditions needed for the members of the team, so they will have competency in teamwork. The application of team work is used by many organization, but a little consequences about readiness of team players. The review of these conditions especially is limited for interpersonal conditions which are needed for the members of the team, and the conditions such as: (1) suitable personality; (2) competency to solve the conflicts (3) collaborative problem solving; and (4) communication. Beside that it also reviews about the development of every individual member to be a team player from the sight point of human resources management, such as (1) recruitment; (2) training; (3) performance appraisal; (4) career development; (5) compensation, and (6) job analysis.The research used literature study of several scrunities about teamwork and human resources management. The conclusion is that human resources management practice could used as tools to create team player competences.